2021
DOI: 10.3390/ijms221910621
|View full text |Cite
|
Sign up to set email alerts
|

Post-Embryonic Lateral Organ Development and Adaxial—Abaxial Polarity Are Regulated by the Combined Effect of ENHANCER OF SHOOT REGENERATION 1 and WUSCHEL in Arabidopsis Shoots

Abstract: The development of above-ground lateral organs is initiated at the peripheral zone of the shoot apical meristem (SAM). The coordination of cell fate determination and the maintenance of stem cells are achieved through a complex regulatory network comprised of transcription factors. Two AP2/ERF transcription factor family genes, ESR1/DRN and ESR2/DRNL/SOB/BOL, regulate cotyledon and flower formation and de novo organogenesis in tissue culture. However, their roles in post-embryonic lateral organ development rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Thus, chromatin accessibility and H3K27me3 coordinately regulate the organ identity gene's activation potential, while chromatin accessibility but not H3K27me3 mediates repression is indispensable for totipotency gene silencing. Indeed, several regeneration-related factors, such as REV [39], SAUR41 [40], CKX7 [41], and DDM1 [42], were gradually diminished during embryo maturation along with closing chromatin status but activated during the callus induction process (Fig. 6d).…”
Section: Chromatin Condensation Associated With Totipotency Reduction...mentioning
confidence: 99%
“…Thus, chromatin accessibility and H3K27me3 coordinately regulate the organ identity gene's activation potential, while chromatin accessibility but not H3K27me3 mediates repression is indispensable for totipotency gene silencing. Indeed, several regeneration-related factors, such as REV [39], SAUR41 [40], CKX7 [41], and DDM1 [42], were gradually diminished during embryo maturation along with closing chromatin status but activated during the callus induction process (Fig. 6d).…”
Section: Chromatin Condensation Associated With Totipotency Reduction...mentioning
confidence: 99%
“…To identify HDA6-interacting proteins, we carried out yeast two-hybrid (Y2H) screening using a commercial cDNA library ( Matiolli and Melotto, 2018 ). Preliminary results suggested that HDA6 interacts with ESR2, which is involved in in vitro plant regeneration ( Ikeda et al., 2006 , 2021 ; Nag et al., 2007 ; Matsuo et al., 2011 ). To validate this observation, we designed and co-expressed the GAL4 DNA-binding domain–HDA6 fusion construct with a construct comprising the GAL4 activation domain fused to full-length ESR2 coding sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Out of ten genes upregulated in response to EPFL6, none were upregulated when EPFL6 was applied with CHX, suggesting that upregulation of these genes is an indirect response to EPFL6. Two upregulated genes with the lowest FDR were DORNROSCHEN (DRN)/ ENHANCER OF SHOOT REGENERATION (ESR1) (AT1G12980) and DRN-LIKE ( DRNL )/ ESR2 (AT1G24590) (Fig 2A), both APETALA2/ETHYLENE RESPONSE FACTOR (AP2/ERF) transcription factors that regulate meristem maintenance and organ initiation (Kirch et al, 2003; Ikeda et al, 2006; Ikeda et al, 2021). But both of these genes were downregulated by EPFL6 in the presence of CHX (Fig.…”
Section: Resultsmentioning
confidence: 99%